Neighborhood Problems in Apartments and Ethical solutions for Them - ali malakoutinia; mohammad taghi sobhaninia (اخلاق وحیانی, 2017)
In the contemporary world, especially in urbanized areas, significant changes have taken place that makes bad effects on neighbors’ relationships, in particular for whom live in apartments. In the present study, with the help of a descriptive-analytical method, we will investigate three threats that endanger apartment-living in urbanized areas: the lack of communication and constructive interaction with neighbors, weakness of participation in the management of apartment shared affairs, and neighborly disturbances, for which we will suggest some ethical solutions. The most important solutions include increasing the neighbors' awareness of each other's status and mutual rights, observing ethical principles in managing the shared affairs of the apartment, understanding the inevitability of some disturbances in neighborly life, adhering to neighborly ethics, and finally appealing to jurisdiction (the last resort) by trying to revive friendship and brotherhood.